2019
DOI: 10.3168/jds.2019-16334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant bovine interleukin-8 (rbIL-8) treatment on health, metabolism, and lactation performance in Holstein cattle I: Production and functional characterization of rbIL-8 in vitro and in vivo

Abstract: In the present study, we standardized processes of cloning and purification of recombinant bovine interleukin-8 (rbIL-8) from bacterial culture and assessed its biological activity in Holstein cattle. Plasmid containing a subclone of bovine IL-8 was expressed using Escherichia coli BL21 and cell lysate was purified by chromatography. The presence of rbIL-8 was assessed by Western blot analyses and function was confirmed in vitro using a chemotaxis chamber. Based on optical density values, chemoattractant prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…We demonstrated that our rbIL-8 molecule elicited the expected biological responses: strong chemoattractant properties in vitro and in vivo (following intravaginal and intrauterine administrations). More importantly, systemic, intrauterine, and intravaginal administration of rbIL-8 did not result in detectable undesirable side effects such as fever, increased respiratory rate, dehydration, or signs of pain and discomfort (Bicalho et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…We demonstrated that our rbIL-8 molecule elicited the expected biological responses: strong chemoattractant properties in vitro and in vivo (following intravaginal and intrauterine administrations). More importantly, systemic, intrauterine, and intravaginal administration of rbIL-8 did not result in detectable undesirable side effects such as fever, increased respiratory rate, dehydration, or signs of pain and discomfort (Bicalho et al, 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Our group has developed a recombinant bovine interleukin-8 (rbIL-8) molecule with the original objective of improving postpartum uterine health (Bicalho et al, 2019). We conducted a series of experiments to evaluate the safety of rbIL-8 administration and to assess its biological activity in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-8 is known for his chemoattractant properties toward neutrophils. Intrauterine infusion of recombinant bovine IL-8 (rbIL-8) by [143,144] within 24 h postpartum was reported to increase proportion of neutrophils in the vagina and uterine lumen and lower the prevalence of puerperal metritis in multiparous cows but had no effect on the incidence of retained placenta. The reader is referred to [145] for more details on this field of research.…”
Section: Other Non-conventional Treatments Of Uterine Infectionsmentioning
confidence: 99%
“…It should be noted that the microbiota of the vaginal tract of dairy cows is not dominated by Lactobacillus strains as is the vaginal tract of female subjects [148]. There is also a difference in the vaginal pH between dairy cows and human vaginal pH, with cows having a slightly acidic to slightly alkaline neutral or slightly alkaline value (pH 6.8-7.35) and humans having an acidotic vaginal pH (3.5-4.5) [143]. Lactobacilli are known to produce lactic acid through hydrolysis of glycogen present in vaginal mucosa and lower the vaginal pH to acidic values, which is unique to humans [148].…”
Section: Intravaginal Probiotics: a New Approach To Preventing Uterine Infectionsmentioning
confidence: 99%
See 1 more Smart Citation